Plan De Auditoría Para Mejorar El Sistema De Gestión De Seguridad Y Salud Ocupacional En Empresa Especializada Consem E.I.R.L. – Pataz - Gonza Llaque, Renzo Rodrigo Andre (2017)
At the global level, it is becoming a trend for mining companies to adopt a system of Occupational Health and Safety Management according to international standards, so that in all areas of the Horizon Mining Company and its contratists, in this case The company CONSEM EIRL, was audited to see their behavior in occupational health and safety, faults and deficiencies to control safety, especially the absence of control tools, to eliminate, reduce and minimize the occurrence of incidents and accidents . Owing mainly to the lack of an adequate occupational health and safety management system, it was in fact incomplete. Finally, through internal audit, critical system points are identified and important factors that help us improve safety at the mine, such as the measurement of safety indexes, timely identification of nonconformities and then take corrective measures to prevent The occurrence of unwanted Incidents / Accidents; This is why the Audit Plan will allow the reduction of the Accidentability Index, given that the General Management is committed and involved in providing a safe and healthy environment to all its workers and people committed to direct and indirect productive process, as well Like the visitors, suppliers and people of the surroundings.